A strategic approach to the future of flat glass industry in Turkey - Tahmiscioğlu, Demet (My University, 1997)
unknown
Keywords: Cam; CAM SANAYİ-TÜRKİYE; Kimya mühendisliği ve ilgili konular; Seramik ve ilgili teknolojiler